2012
DOI: 10.1016/j.brainres.2012.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lesions of the amygdala central nucleus on autoshaped lever pressing

Abstract: Neutral cues paired with rewards often appear to acquire motivational significance, as if the incentive motivational value of the reward is transferred to the cue. Such cues have been reported to modulate the performance of instrumental action (Pavlovian-instrumental transfer, PIT), serve as conditioned reinforcers in the establishment of new learning, and be the targets of approach and other cue-directed behaviors. Here we examined the effects of lesions of the amygdala central nucleus (CeA) on the acquisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 37 publications
(65 reference statements)
7
40
1
Order By: Relevance
“…As in previous autoshaping studies [5,6], peak lever press responding was observed during the 2 nd 5 s of CS presentations. Table 1 presents the mean lever press rate and percentage of trials with a lever press of OFC- and sham-lesioned rats during the first and second 5 s intervals of CS+ and CS- presentations, averaged over the entire training period.…”
supporting
confidence: 74%
“…As in previous autoshaping studies [5,6], peak lever press responding was observed during the 2 nd 5 s of CS presentations. Table 1 presents the mean lever press rate and percentage of trials with a lever press of OFC- and sham-lesioned rats during the first and second 5 s intervals of CS+ and CS- presentations, averaged over the entire training period.…”
supporting
confidence: 74%
“…The CeN is required to learn from (negative) reward-prediction error (Holland and Gallagher 1993;Holland et al 2001;Haney et al 2010) and CeN-SNc-projecting neurons will become activated after learning by reward-prediction error, suggesting that communication between these structures relates to reward-prediction errormediated learning (Lee et al 2010). An intact CeN is also required for the acquisition of conditioned-orienting (Gallagher et al 1990) and sign-tracking responding (Parkinson et al 2000), but is not required for more specific consummatory CRs (Chang et al 2012). Similarly, the CeN is required for general, but not outcome-specific PIT (Hall et al 2001;Holland and Gallagher 2003;Corbit and Balleine 2005).…”
Section: Circuitry For General Motivational Valuementioning
confidence: 99%
“…Nevertheless, we suggest the maintenance of approach behaviors are best captured by incentive motivation concepts, which suggest that such sign-tracking CRs occur because of a motivational attraction to the CS+, a motivation that can become decoupled from trial-to-trial variations in reward outcome. The fact that rats persisted in engaging with the CS+ instead of favoring the food cup lends further support to the argument here that the incentive value of the CS+ remained high.In the brain, limbic circuits have been implicated in signtracking (Cardinal et al 2002;Mahler and Berridge 2009;Flagel et al 2010;Chang et al 2012a Chang et al ,b, 2015Saunders and Robinson 2012;Chang and Holland 2013). A fruitful effort would be to resolve the neural mechanisms by which rats adaptively modify their responses when CS -CR -US conditions change but CS incentive salience remains strong.…”
mentioning
confidence: 99%
“…In the brain, limbic circuits have been implicated in signtracking (Cardinal et al 2002;Mahler and Berridge 2009;Flagel et al 2010;Chang et al 2012a Chang et al ,b, 2015Saunders and Robinson 2012;Chang and Holland 2013). A fruitful effort would be to resolve the neural mechanisms by which rats adaptively modify their responses when CS -CR -US conditions change but CS incentive salience remains strong.…”
mentioning
confidence: 99%